Which Governance Mechanisms Promote Efficiency in Reaching Poor Clients? Evidence from Rated Microfinance Institutions - Valentina Hartarska; Roy Mersland (European Financial Management, 2012)
This paper evaluates the effectiveness of several governance mechanisms on microfinance institutions' (MFI) performance. We first define performance as efficiency in reaching many poor clients. Following the literature on efficiency in banks, we estimate a stochastic cost frontier and measure output by the number of clients. Therefore, we capture the cost minimisation goal and the goal of serving many poor clients, both of which are pursued by MFIs. We next explore the impact of measurable governance mechanisms on the individual efficiency coefficients. The results show that efficiency increases with a board size of up to nine members and decreases after that. MFIs in which the CEO chairs the board and those with a larger proportion of insiders are less efficient. The evidence also suggests that donors' presence on the board is not beneficial. We do not find consistent evidence for the effect of competition, and we find weak evidence that MFIs in countries with mature regulatory environments reach fewer clients, while MFIs regulated by an independent banking authority are more efficient.
Keywords: 650